Mitigation of scale problem in the pumped Disi water to Amman, Jordan - Al-Maabreh, Alaa M.; Al-Rawajfeh, Aiman Eid; Alshamaileh, Ehab; Al-Bazedi, G. A. (Oficyna Wydawnicza Politechniki Wrocławskiej, 2019)
Various methods are known to mitigate or prevent scale formation in pipes, rather by chemical addition, e.g., anti-scaling substances, or physically which includes ultrasonic or nanofiltration (NF). Nanofiltration membranes have a selectivity for the multivalent charged ions, so monovalent ions will pass the membrane partly and multivalent ions will be rejected completely. Chemical addition to prevent scale formation is based on justifying water parameters such as pH, alkalinity, and concentrations of ions that form the building units of scale crystal. In order to mitigate the scaling tendency in water pumped from the Disi aquifer to Amman city along its 345 km pipeline, different studies were conducted using simulated plumbing system. This part of the study is concerned with scale mitigation using nanofiltration and addition of chemicals. Nanofiltration was applied to reduce the hardness that causes scale deposition where it rejected around 70.5% of Ca2+, 71.98% Mg2+, 7.72% K+, 29.0% Na+, 66.63% Cl–, 86.51% NO3 – , 85.72% SO4 2–, and 69.85% CO2. Increasing the concentration of some ions such as Na+, K+ and Cl– keeping the allowable limit gave good results for scale mitigation.
Environment Protection Engineering. Vol. 45, 2019, nr 1, s. 97-110
Keywords: ochrona środowiska; inżynieria środowiska